Analisis Konflik pada Tokoh Utama Dalam Novel Saat-saat Jauh Karya Lia Seplia - Sari, Yolanda; Murniviyanti, Liza; Wanadiyo, Wanadiyo (Institut Teknologi Pendidikan Indonesia, 2022)
The conflict that man experiences in his life often appeal to literature to assign them to literary works. Literary works provided a literary tool for presenting the conflict that man experiences in his life. The censure of conflict themes as central themes can be seen in novels already existing, among other things, in lia seplia distant moments. The problem of research is (1) how does a protagonist’s conflict in a novels moments away by lia seplia? (2) are the factors behind a protagonist’s conflict in a lia seplia paperback novel? The study aims (1) to identify and describe a conflict of main characters in lia seplia distant novels; (2) to describe the factors behind a leading character conflict in lia seplia distant novels. The method used is a descriptive method with a qualitative approach. Data collection using documentation. The technique used to analyze data for this study is the analtsis of content. Studies and discussions suggest that the main character’s appearance of conflict split into two, physical and psychic conflicts. A physical conflict divides into a conflict with the environment. Inner conflict manifests itself in conflicts that stem from personal feelings and those that come from thefeelings of others. The factors affecting the novel’s protagonist’s conflict are divided into two types of internal and estern factors. Internal factors manifest themselves, including the events of the main character, the ekstern factor is manifest in the environment and in others.